Antineoplastic Agents and the Associated Myelosuppressive Effects: A Review. (October 2014) - Barreto, Jason N.; McCullough, Kristen B.; Ice, Lauren L.; Smith, Judith A.
Bone marrow is a complex organ responsible for the regulation of hematopoietic cell distribution throughout the human body. Patients receiving antineoplastic agents as a therapeutic intervention for hematologic malignancy often experience varying degrees of myelotoxicity. Antineoplastic agents cause hypocellularity in marrow resulting in a reduction in hematopoietic tissue activity and a corresponding decline in cell production. Quantifying the adverse effects on hematopoiesis is based on the properties of a single agent, the use of individual drugs within a combination chemotherapy regimen, and the course, or courses, of chemotherapy designed to treat cancer. The direct or indirect suppression of erythrocytes, granulocytes, and megakaryocytes has potential for multiple negative clinical consequences ranging from increased monitoring of blood counts to life-threatening infection and death. This review will provide an overview of the structure and function of competent adult bone marrow, describe the process of hematopoiesis, and characterize the myelotoxicities associated with common antineoplastic agents currently used in the treatment of cancer.